PENGARUH MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE STAD TERHADAP MINAT BELAJAR SEJARAH SISWA SMA NEGERI 2 BONTANG - Rahayu, Dian Budi; Norhidayat (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This research aims to determine the influence and how significant the influence of the Student Teams Achievement Division learning method is on students' interest in learning in history subjects at SMAN 2 Bontang. This approach uses a quantitative approach with experimental methods. The research design used was a posttest – only control design. The samples used were two classes, namely the experimental class (X1) and the control class (X2). Data collection uses a questionnaire. This research also uses several data analysis methods, namely Normality Test, Linearity Test and Regression Hypothesis Test with the help of SPSS 27. The results of the hypothesis testing research carried out based on the coefficient data obtained a significance value of 0.000. From the data, the significance was 0.000 <0.05, so Ho was rejected. Because Ho is rejected, Ha is accepted, so there is an influence of the relationship between the Student Teams Achievement Division learning method on students' interest in learning. The coefficients for the variables X and Y in the experimental 0,956 class are categorized as having a very strong correlation level, namely in the range 0,8 – 1,00. This proves that students need learning models that are more interesting, creative and innovative in helping teachers convey learning material in the classroom. And the Student Teams Achievement Division learning method can be used in the history learning process in the classroom.